The therapeutic relationship in the care of a bipolar affective disorder carrier: a transforming experience - Ana Claudia Silva Lemos; Marcio Flávio Moura de Araújo; Carolina Maria de Lima Carvalho; Angélica Mota Marinho (Rev Rene)
The consolidation of the conjectures of the Psychiatric Reformation has continuously changed assistance and teaching of mental health. The purpose of the study is to refer to an academic experience of psychiatric nursing assistants, intermediated by the process of Therapeutical Relationship commended by Stefanelli to a customer with Bipolar Affective Disorders (BAD) during a ten day meeting in a one Hospital-Day in Fortaleza. The method used for data collection was the participant observation, field experiment and the nursing reporting. After facing the case reported, it was observed that the BAD is a multifactorial character psychopathology, so that it is required from the nurse an integrated vision concerning care implementation.. By this perspective the Therapeutical Relationship was a method used to promote a brief but transforming and stimulating bond of thoughts, attitudes and reflections in the customer. The experience was quite important, still in the modification of personal paradigms concerning psychiatric assistance as well and in the understanding of the human being sanity ephemerality.